Rastreabilidade de farinhas de origem animal em ovos de poedeiras comerciais pela técnica dos isótopos estáveis do carbono 'delta' 'INTPOT.13 C' do nitrogênio 'delta' 'INTPOT.15 N' - Denadai, Juliana Célia [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The aim of this study was to trace the inclusion of bovine meat and bones meal (BMBM) in diets of laying hens analyzing eggs and theirs fractions (yolk and albumen), by carbon (δ13C) and nitrogen (δ15N) stable isotopes, as well as to evaluate the detectable analytical minimal index. Two hundred forty (240) Shaver White laying hens aging 73 weeks never fed with animal origin ingredients were randomly distributed in five treatments and fed with a corn and soybean based diet (control) and four increasing levels (0; 1.5; 3.0; 4.5 and 6.0%) of BMBM. At the 35th day, 24 eggs per treatment were randomly collect, twelve for yolk and albumen sampling and twelve for egg (yolk + albumen) sampling. The isotopic results were analyzed in a multivariate analysis of variance. Through an error matrix (95% confidence) the ellipses were determined to identify the differences among the treatments (diets BMBM inclusion) from the control group (0% BMBM group). It was possible to detect BMBM inclusion through the isotopic pair of yolk and egg at 3.0% of inclusion. In the albumen it was possible to detect the 1.5% BMBM inclusion. In summary, the stable isotopes technique is able to trace BMBM in laying hens feed, in the final product at a minimal level of inclusion of 1.5% in the albumen and 3.0% in the egg and yolk.
Keywords: Galinhas; Farinha de carne e ossos bovina - Dieta de poedeiras; Bovine meat and bones meal - Diets of laying hens